2x + 3y = 3
-10x + 2y = -32
Solve using the substitution method.
Solve for x in the first equation.
2x + 3y = 3
Subtract 3y from both sides.
2x = 3 - 3y
Divide both sides by 2.
x =
-
y
Plug x into the second equation.
-10(
-
y) + 2y = -32
Distribute -10 inside the parentheses.
-15 + 15y + 2y = -32
Combine like terms.
-15 + 17y = -32
Add 15 to both sides.
17y = -17
Divide both sides by 17.
y = -1
Plug y into the first equation.
2x + 3(-1) = 3
Multiply 3 by -1.
2x - 3 = 3
Add 3 to both sides.
2x = 6
Divide both sides by 2.
x = 3
x = 3;
y = -1